Pendekatan Manajerial Guru Akidah Akhlak dalam Pengembangan dan Pembentukan Nilai Moral Siswa - Ali Anwar, Muhamad (Kartika: Jurnal Studi Keislaman, 2025)
Morality is defined as human behavior or character that reflects the rightness or wrongness of actions. Moral education is essential for students as it plays a crucial role in shaping individuals with noble character (akhlakul karimah). One approach to moral education in schools is through habituation of religious culture, utilizing modeling and routine practice. This study aims to analyze the managerial approach of Akidah Akhlak teachers in developing and fostering students’ moral values. The method employed is a library research (library research) with a qualitative descriptive approach. Data were collected from books, journals, and academic sources related to Akidah Akhlak education and character development. The results indicate that moral education can be implemented through three main aspects: (1) teacher strategies in instilling moral values through modeling and habituation, (2) planning that includes the preparation of teaching materials and methods, and (3) implementation emphasizing students’ direct practice in daily life, such as waking up on time, performing five daily prayers, obeying parents and teachers, and avoiding prohibited actions. By applying an effective managerial approach, students can internalize moral values from an early age and develop good and noble character.